14.0k views
4 votes
PLEASE HELP

Look at the proof showing sin^4x=3-4cos2x+cos4x/8. Which expression will complete the fourth step of the proof?
sin^4x=(sin^2x)^2
sin^4x=(1-cos2x/2)^2
sin^4x=1-2cos2x+cos^22x/4
sin^4x=?
A.) 1-2cos2x+(1+cos4x/2)/4
B.)1-2cos2x+1+cos4x/4
C.)1-2cos2x+(1+cos2x/2)/4
D.)1-2cos2x+1-cos2x/4

User AXO
by
5.6k points

2 Answers

6 votes

A
p/s : follow me and I will help you more about maths :))))
PLEASE HELP Look at the proof showing sin^4x=3-4cos2x+cos4x/8. Which expression will-example-1
User DanMad
by
6.0k points
4 votes

Answer:

Option 1 is correct.

Explanation:

Given the expression


sin^4x=(1)/(8){(3-4cos2x+cos4x)}

we have to complete the fourth step to prove the above result.


sin^4x=(sin^2x)^2\\\\sin^4x=((1-cos2x)/(2))^2 \\\\sin^4x=(1-2cos2x+cos^22x)/(4)

As,
cos^2x=(1+cos2x)/(2)


cos^(2)2x=(1+cos4x)/(2)

Hence, the next step becomes


sin^4x=(1-2cos2x+(1+cos4x)/(2))/(4)

Hence, option 1 is correct.

User Vamsi
by
6.6k points